BERAT BADAN AKHIR, KONVERSI RANSUM DAN INCOME OVER FEED AND CHICK COST AYAM BROILER DENGAN PEMBERIAN RANSUM KOMERSIAL - Kiramang, Khaerani (Fakultas Sains dan Teknologi UIN ALauddin, 2011)
The aim of this study to determine the effect of feeding commercial rations on the final live weight, feed conversion and